Inverse Stackelberg Solutions for Games with Many Followers - Yurii Averboukh (Mathematics, 2018)
The paper is devoted to inverse Stackelberg games with many players. We consider both static and differential games. The main assumption of the paper is the compactness of the strategy sets. We obtain the characterization of inverse Stackelberg solutions and under additional concavity conditions, establish the existence theorem.